PERAN GURU BIMBINGAN KONSELING DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS SISWA KELAS V DI MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Umimah, Sovia; Mardani, Dadan; Humaeroh, Iis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to describe the role of guidance and counseling (BK) teachers in improving the psychological well-being of fifth-grade students at Madrasah Ibtidaiyah Ma’had Al-Zaytun. It also identifies the strategies used and the factors influencing students’ psychological well-being. This study applied a qualitative descriptive approach. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The findings reveal that BK teachers play multiple roles as counselors, facilitators, motivators, mediators, and role models in guiding students to manage emotional and social challenges. Implemented strategies include personal, social, learning, and career guidance; motivational encouragement; and the creation of a supportive learning environment. Internal factors such as emotion, motivation, self-confidence, and spirituality, and external factors such as family support, school environment, social interaction, and economic background, strongly influence students’ psychological well-being. The active involvement of BK teachers positively contributes to emotional stability, motivation, and social adaptability among students. The study recommends that schools employ professional BK teachers to ensure the sustainability of counseling services and the development of students’ holistic well-being.